Praktik Muḍārabah di Bank Muamalat KCP Wonosobo Perspektif Hukum Ekonomi Syariah - Fathudin Fathudin; Adi Wibowo; Salsabella Rahma Dewi (Prodi Hukum Keluarga Fakultas Agama Islam Universitas Nurul Jadid, 2020)
This research discusses the practice of muḍārabah at Bank Muamalat, Wonosobo Sub-Branch Office, a form of business collaboration using a muḍārabah contract and in the process the business fails so that it suffers losses caused not by the negligence of the fund manager (muḍārib) so the fund manager must bear all the losses. Where it should be in the syari'ah concept that if you collaborate using the muḍārabah agreement, if the business fails in the process, the loss is fully borne by the owner of the capital (ṣāḥibul māl). Discussion of the theory and practice in the muḍārabah contract according to Islamic law is very important. This study aims to determine the law regarding the practice of muḍārabah financing at the Bank Muamalat Wonosobo Branch Office, whether it is legal or not legally '. The approach used uses a normative approach with the object of the muḍārabah contract practice at the Bank Muamalat Wonosobo Branch Office which is adjusted to the perspective of Islamic law. After conducting an analysis with adjustments between Islamic Law and collaboration products with the muḍārabah agreement implemented by the Bank Muamalat Wonosobo Branch Office, it resulted in a conclusion that the practice of the muḍārabah contract was not in accordance with Islamic Law (syara ').